2019
DOI: 10.1002/cam4.1985
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of DNA viruses from posttransplant lymphoproliferative disorders

Abstract: Posttransplant lymphoproliferative disorders (PTLDs), 50%‐80% of which are strongly associated with Epstein‐Barr virus (EBV), carry a high morbidity and mortality. Most clinical/epidemiological/tumor characteristics do not consistently associate with worse patient survival, so our aim was to identify if other viral genomic characteristics associated better with survival. We extracted DNA from stored paraffin‐embedded PTLD tissues at our center, identified viral sequences by metagenomic shotgun sequencing (MSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
(53 reference statements)
2
6
0
Order By: Relevance
“…Previous full genome sequencing studies of EBV in PTLD were restricted to cell lines derived from PTLD patients (9) or FFPE PTLD specimens (16) and did not include non-PTLD transplant controls. Consistent with our findings, Dharnidharka et al (16) also found that EBNA3C, as well as EBNA1 and EBNA-LP, isolated from FFPE specimens had increased numbers of variations compared with other EBV genes; however, the specific variations were not reported. Interestingly, the Ala-683Val and Glu701Gln variations in EBNA3C that we identified from the blood of PTLD subjects were also identified in some PTLD-derived B cell lines (9).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous full genome sequencing studies of EBV in PTLD were restricted to cell lines derived from PTLD patients (9) or FFPE PTLD specimens (16) and did not include non-PTLD transplant controls. Consistent with our findings, Dharnidharka et al (16) also found that EBNA3C, as well as EBNA1 and EBNA-LP, isolated from FFPE specimens had increased numbers of variations compared with other EBV genes; however, the specific variations were not reported. Interestingly, the Ala-683Val and Glu701Gln variations in EBNA3C that we identified from the blood of PTLD subjects were also identified in some PTLD-derived B cell lines (9).…”
Section: Discussionsupporting
confidence: 91%
“…These variant peptides may constitute tumor neoantigens that could be exploited to augment cellular immunotherapy approaches. Using previously established classification schemes for EBV strains, we found that all EBV genomes isolated from the blood of PTLD patients were type 1, consistent with prior reports that type 1 is prevalent in EBV isolated from FFPE specimens of PTLD patients (16,34). In contrast, 4 of the 6 strain types defined by LMP1 diversity were represented in PTLD-derived EBV genomes (11).…”
Section: Discussionsupporting
confidence: 87%
“…We developed ViroMatch to analyze data sets of millions of short metagenomic sequence reads to identify viruses by sensitive sequence alignment using pragmatic system resources. We have modified and refined our analysis pipeline workflow over time, primarily applied to the analysis of vertebrate viruses ( 9 16 ). The latest version is made available to the public for the first time here.…”
Section: Announcementmentioning
confidence: 99%
“…Post-transplant lymphoproliferative disorder (PTLD) is a complication of hematopoietic stem cell (HSCT) and solid organ transplantation associated with high morbidity and mortality [ 1 , 2 , 3 , 4 ]. These lymphoid and/or plasmacytic proliferations comprise a broad morphological spectrum, ranging from Epstein–Barr virus drive hyperplasia to malignant monoclonal proliferations, histologically indistinguishable from B-cell (or less commonly T/NK-cell) lymphomas in immunocompetent patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%